The Effect of Internet Usage on Social Capital in Indonesia - Neno Prayitno; Khoirunurrofik Khoirunurrofik (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2020)
The development capital consists of financial capital, physical capital, human capital, and social capital. Social capital focuses on efforts to empower social relations. The relationship between social capital and ICT, especially the internet, has become an interesting debate. In fact, several studies have been conducted with quite diverse findings. The internet is able to connect people who are far from each other, but on the other hand, it often makes people who are physically close to each other seem far apart. This study aims to examine the effect of internet use on social capital in Indonesia. The data is obtained from the fifth Indonesian Family Life Survey (IFLS-5). The study found that in general, internet users have lower social capital than non-internet users. Likewise, highly educated people have higher social capital than people with low education. Then, internet users with higher education have higher social capital when compared to internet users with lower education. This means that the use of the internet must be accompanied by the readiness of human resources (digital literacy) in accepting new technology, filtering the flow of incoming information, and educating the public about how to use the internet in healthy, safe, and wise manner.